2023
DOI: 10.1111/rec.13892
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary succession—do we really need the new term? Response to Rapson (2023)

Abstract: The term tertiary succession which follows restoration measures was introduced recently as a complement to primary and secondary succession. However, its widespread use is not justified ecologically. It seems rather formalistic and does not contribute to a better linking of successional theory and practical ecological restoration. The arguments questioning the use of this term are summarized here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Of course, the arrangement of species chosen for use in the restoration and their behavior in the area are crucial to obtaining such environmental characteristics. From this perspective, the species in this study that showed greater local suitability, such as A. glandulosa, I. edulis and M. coriaceae (1,4,8) are suitable for strategic use in the restoration of areas dominated by invasive exotic grasses (Urochloa sp. ), given their potential to contribute to the vertical and horizontal structure of the forest.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of course, the arrangement of species chosen for use in the restoration and their behavior in the area are crucial to obtaining such environmental characteristics. From this perspective, the species in this study that showed greater local suitability, such as A. glandulosa, I. edulis and M. coriaceae (1,4,8) are suitable for strategic use in the restoration of areas dominated by invasive exotic grasses (Urochloa sp. ), given their potential to contribute to the vertical and horizontal structure of the forest.…”
Section: Discussionmentioning
confidence: 96%
“…In recent decades, restoration has assumed an ascending role associated with sustainable development and the ecology of restoration in which it is critical to prepare for the uncertain effects of climatic change on ecosystem functioning and socially relevant services [4,5]. The world is committed to restoring millions of hectares of forest as a strategy to mitigate climate change with many other co-benefits, although the suitability of climatic conditions for the trees being planted at the restoration sites is changing, which may reduce the long-term viability of these projects [6,7].…”
Section: Introductionmentioning
confidence: 99%